Follow-up study of depression in the elderly. Clinical and SPECT data. - Halloran, E; Prentice, N; Murray, C; O'Carroll, R; Glabus, M; Goodwin, G; Ebmeier, K (1999)
BACKGROUND: Imaging studies in depression of the elderly are often small and highly selective. AIMS: To investigate a large group of elderly depressed patients in order to assess changes in clinical, imaging and neuropsychological variables at follow-up. METHOD: Patients (n = 175, age range 65-91 years) with clinical depression were identified from consecutive local referrals. Clinical interviews, neuropsychological tests and SPECT scans were carried out at referral and at two-year follow-up. RESULTS: Of 84 re-examined patients, 46.5% were well, 9.5% were ill, 33% partially recovered and 11% had developed dementia. Duration of illness before index assessment was the only factor to predict outcome. Thirty-nine patients could be scanned and followed up. There were no differences between patients with good or poor depressive outcome on SPECT. Ten clinically improved patients could be re-examined with SPECT. There were relative increases in right cingulate gyrus and right cerebellum at follow-up. CONCLUSIONS: The patients group was comparable with other studies showing high levels of residual depressive symptoms. Activity changes in limbic cortex are implicated in depression of old age.